Rural Social Innovation: An Exploratory Study in Rural Brazil - Santo, Anderson; Andion, Carolina (Organizações & Sociedade, 2025)
The purpose of this study is to understand how social innovations occur in rural areas – what facilitates and/or hinders them – and how they affect rural development. To achieve this, a systematic review was conducted to identify the current state of the discussions surrounding social innovation in rural areas, followed by extensive ethnographic fieldwork to examine the practices promoted by families living in the rural settlement of Taquaral, located in Corumbá, within the Pantanal region of Mato Grosso do Sul. Using an analytical and methodological approach built under the aegis of the sociology of public problems, with a pragmatist basis, and considering settlements as laboratories for experimentation, the main findings indicate that rural social innovation is a powerful instrument for addressing the socio-environmental challenges that affect rural families and can provide vitality to rural development. However, studying social innovation requires robust fieldwork to capture how it unfolds. After all, much more than the dissemination of techniques, it emerges from the collective confrontation of various problematic situations that affect actors over time.